Dose dependence of diethylnitrosamine-induced nuclear enlargement in embryonal turkey liver - Enzmann, Harald G.; Kühlem, Christiane; Löser, Eckhard; Bannasch, Peter (Carcinogenesis, 1995)
Avian embryos (turkey) were exposed to diethylnitrosamine in ovo. On the first day of incubation doses of 0.5-5.0 mg/ egg were injected into the white of the fertilized egg. The experiment was terminated 4 days before hatching. Livers were removed and prepared for subsequent histological examination. In haematoxylin and eosin stained sections the areas of hepatocyte nuclear profiles were measured by semi-automatic image analysis. In liver samples of diethylnitrosamine-exposed embryos hepatocyte nuclei of more than twice the size of normal hepatocyte nuclei were found. The incidence of the enlarged nuclei was clearly dose dependent. An increase in the size of hepatocyte nuclei was observed after low doses of diethylnitrosamine that did not induce common signs of non-specific toxic effects, e.g. cell death, fat vacuoles or loss of glycogen. The slope of the dose-response curve was rather steep. A 10-fold increase in the dose of the carcinogen resulted in a 100-fold increase in the incidence of enlarged hepatocyte nuclei. In combination with preneoplastic foci of altered hepatocytes, the quantification of nuclear enlargement can provide a valuable complementary parameter for the evaluation of carcinogen-induced effects in ovo.